Histomorphological and histochemical study of stomach of domestic pigeon (Columba livia domestica): F. J. Al-Saffar1 and Eyhab, R. M. Al-Samawy2 - Al-Saffar, F. J. (The Iraqi Journal of Veterinary Medicine, 2016)
The study aimed at describing the histomorphological and histochemical structures of the stomach wall in domestic pigeon. Twelve healthy birds were collected from local suppliers at Baghdad province. Birds were divided into three equal groups for gross, histological and histochemical approaches. All birds were euthanized and their abdomens were dissected, then their stomachs were identified and photographed in situ. Specimens from stomach were fixed as well and then processed for histological and histochemical staining techniques using Hematoxylin-eosin, Masson Trichrome, Periodic acid Schiff (PAS) and PAS -Alcian blue (AB) (pH 2.5). Grossly the stomach of the pigeon consisted of two distinguishable chambers, that were glandular or proventriculus and muscular or ventriculus. The proventriculus was tubular-shaped organ. Whereas, the ventriculus appeared fusiform in shape and surrounded by considerable amount of fatty tissue. Histologically the proventriculus mucosal lining was simple columnar epithelium cells. The submucosal consists of numerous and voluminous deep submucosal glands which occupied the greater part of the organ wall. The internal lining of the ventriculus was simple columnar cells. Muscularis mucosa appeared circularly arranged bundles interrupted by the presence of mucosal glands in the lamina propria. The tunica muscularis appeared as a very thick structure of smooth muscles fibers of three layers, thin inner, outer longitudinal and very thick intermediate circular layers.